Nitrogênio e idade de corte na qualidade da biomassa de capimelefante para fins agroenergéticos cultivado em Latossolo - Flores, Rilner Alves; Urquiaga, Segundo; Alves, Bruno José Rodrigues; Collier, Leonardo Santos; Zanetti, Juliano Brás; De Mello Prado, Renato [UNESP] (Universidade Estadual de Londrina, 2013)
Nowadays one of the major challenge for research is the production of alternative agrifuels energy material derived from plant biomass. Allied to this, the proper management of nitrogen, becomes fundamental for productivity gains and improvement in quality of elephant grass biomass. Thus, the objective was to evaluate the effect of nitrogen fertilization and plant age effect on the quality of elephant grass biomass for energy purposes. The experiment was performed with genotype Paraíso, grown in a dystrophic Oxisol in the southern state of Tocantins. The design was randomized blocks with subdivided plots, situating plots as nitrogen rates (0, 50, 100 and 150 kg ha-1) and the subplots cutting age (120, 150 and 180 days after planting ) four replicates. We evaluated the relationship carbon/nitrogen (C:N) and leaf/stem (L:S), levels of neutral detergent fiber (NDF) and ash contents in dry biomass produced. The application of nitrogen increased by 12% to C:N ratio of the plant. The advanced age of cut forage was increased 9% in the C:N plant, however, decreased by 12 and 14% levels of ash produced in the stem and leaves, respectively. The production of elephant grass for agrifuels is feasible with management system proposed, quality characteristics desirable, such as high C:N ratio, above 40% and higt fiber content, above 50%.
Nitrogen and age on the quality of elephant grass for agroenergy purpose grown in Oxisol
Keywords: Bioenergy; Nitrogen fertilization; Pennisetum purpureum